From synchrotrons for XFELs: the soft x-ray near-edge spectrum of the ESCA molecule. (2nd December 2020) - Sorensen, S L; Zheng, X; Southworth, S H; Patanen, M; Kokkonen, E; Oostenrijk, B; Travnikova, O; Marchenko, T; Simon, M; Bostedt, C; Doumy, G; Cheng, L; et al.
Abstract: A predictive understanding of soft x-ray near-edge absorption spectra of small molecules is an enduring theoretical challenge and of current interest for x-ray probes of molecular dynamics. We report the experimental absorption spectrum for the electron spectroscopy for chemical analysis (ESCA) molecule (ethyl trifluoroacetate) near the carbon 1s absorption edge between 285–300 eV. The ESCA molecule with four chemically distinct carbon sites has previously served as a theoretical benchmark for photoelectron spectra and now for photoabsorption spectra. We report a simple edge-specific approach for systematically expanding standard basis sets to properly describe diffuse Rydberg orbitals and the importance of triple excitations in equation-of-motion coupled-cluster calculations of the energy interval between valence and Rydberg excitations.